Bioenergetic dysfunction in the pathogenesis of intervertebral disc degeneration - Chao Song; Peixuan Hu; Renpeng Peng; Feng Li; Zhong Fang; Yong Xu (Elsevier, 2024)
Intervertebral disc (IVD) degeneration is a frequent cause of low back pain and is the most common cause of disability. Treatments for symptomatic IVD degeneration, including conservative treatments such as analgesics, physical therapy, anti-inflammatories and surgeries, are aimed at alleviating neurological symptoms. However, there are no effective treatments to prevent or delay IVD degeneration. Previous studies have identified risk factors for IVD degeneration such as aging, inflammation, genetic factors, mechanical overload, nutrient deprivation and smoking, but metabolic dysfunction has not been highlighted. IVDs are the largest avascular structures in the human body and determine the hypoxic and glycolytic features of nucleus pulposus (NP) cells. Accumulating evidence has demonstrated that intracellular metabolic dysfunction is associated with IVD degeneration, but a comprehensive review is lacking. Here, by reviewing the physiological features of IVDs, pathological processes and metabolic changes associated with IVD degeneration and the functions of metabolic genes in IVDs, we highlight that glycolytic pathway and intact mitochondrial function are essential for IVD homeostasis. In degenerated NPs, glycolysis and mitochondrial function are downregulated. Boosting glycolysis such as HIF1α overexpression protects against IVD degeneration. Moreover, the correlations between metabolic diseases such as diabetes, obesity and IVD degeneration and their underlying molecular mechanisms are discussed. Hyperglycemia in diabetic diseases leads to cell senescence, the senescence-associated phenotype (SASP), apoptosis and catabolism of extracellualr matrix in IVDs. Correcting the global metabolic disorders such as insulin or GLP-1 receptor agonist administration is beneficial for diabetes associated IVD degeneration. Overall, we summarized the recent progress of investigations on metabolic contributions to IVD degeneration and provide a new perspective that correcting metabolic dysfunction may be beneficial for treating IVD degeneration.